Micro-phenomenological approach to explore the patient experience during an initial spirometry examination to diagnose COPD in general practice in France. Issue 7 (2nd July 2021) - Bremond, Matthieu; Berthelot, Anthony; Plantier, Laurent; Breton, Hervé; Pautrat, Maxime
Abstract : Objectives: To explore the patient experience of a spirometry test used to confirm chronic obstructive pulmonary disease (COPD) diagnosis in patients with suspected smoking-related COPD. Design: This is a qualitative study, performed with open interviews in adults following a routine spirometry test to confirm COPD diagnosis. Data were analysed with a phenomenological-inspired micro-phenomenology approach. Participants: Eligible patients were recruited through their general practitioner, 10 were interviewed. Setting: Primary care in Centre-Val-De-Loire area, France, in 2018. Results: Participants reported the spirometry test experience as being unfamiliar but gave meaning to the symptoms they experience. Participants expressed a desire to perform the test well and a willingness to confront their state of health. After the spirometry had been completed and the results announced, participants moved through stages of grief from their pre-spirometry self and symptom perception to a state of acceptance. Overall, participants expressed a narrative of an evolving cognitive and corporeal awareness during this spirometry experience. The verbatim quotes describe a cognitive rupture with their chronic illness usually considered as a 'way of life'. Conclusions: A spirometry test goes beyond a diagnostic value, providing patients with an opportunity to gain awareness of their own state of health, reframe their breathlessness-related limitations and thus begin to accept the disease. These awareness gains may be considered as small steps towards health behavioural change. Spirometry may have educative potential and support lifestyle changes.